Identification of serotype O3b and high-risk clone ST37 of Klebsiella pneumoniae revealed by comparative genomic analysis - Sivaraman Gopalan Krishnan; Sudha Sajeev; Visnuvinayagam Sivam; Raja Swaminathan T.; Rakshit Ojha; Bibek Ranjan Shome; Mark Holmes; Thanigaivel Sundaram; Ramesh M. D.; Saranya Vinayagam; Suseela Meesala; Tabarak Malik; et al. (Frontiers in Cellular and Infection Microbiology)
BackgroundEpidemiological risk factors such as the demography of a place, environment, food, livestock, and companion animals are known sources of Klebsiella pneumoniae infection. Whole-genome sequencing (WGS) has become a powerful tool to complement traditional microbiological characterization of foodborne pathogens. Moreover, K. pneumoniae has several species complexes (KpSC) and is very difficult to differentiate using routine microbiological methods. The present study aims to investigate the prevalence of K. pneumoniae in fish available in the retail market using WGS.MethodsIsolation of K. pneumoniae, identification of K. pneumoniae isolates, and determination of the minimum inhibitory concentration (MIC) were performed. Whole-genome sequencing of K. pneumoniae genomes and phylogenomic analysis were conducted for visual comparison of the genomes. Furthermore, genomes of non-human origin that were submitted from India to the NCBI database were downloaded and included in the comparative analysis.ResultsThe findings showed that many antibiotic-resistant genes (ARGs) are prominent, including acrD, BaeR, cpxA, mdtB, mdtC, CRP, H-NS, KpnE, KpnF, KpnG, KpnH, acrA, acrB, marA, ramB, oqxA, oqxB, LptD, and emrR. Four fish-sourced isolates had different blaSHV resistance gene variants. The presence of ARGs for aminoglycosides [aac(3)-IId], fluoroquinolones (oqxA, oqxB), and fosfomycin (fosA5, fosA6) in these K. pneumoniae isolates from fish sources was found. One of the CIFT-K6 isolates had the uncommon serotype of K. pneumoniae O3b with the high-risk clone “ST37.” The ST515 sequence type was present in two K. pneumoniae isolates (CIFT-K7 and CIFT-K8), but the O3b serotype and ST192 allele type were present in the CIFT-K10 isolate.ConclusionTo the best of our knowledge, this research study represents the first Indian report of K. pneumoniae linked to fish, specifically the high-risk clone ‘ST37’ and two other STs, 515 and 192. The most common plasmid type detected in all four isolates was IncFIB, and 75% of the isolates were IncFII and IncHI1B. The prevalence of ARGs linked to efflux pump resistance mechanisms is highlighted by the analysis of genome sequence data.